2020
DOI: 10.1177/0003702820969715
|View full text |Cite
|
Sign up to set email alerts
|

Chemometric Approach to a Rapid Attenuated Total Reflection Fourier Transform Infrared Analysis of Complex Heroin-Based Mixtures

Abstract: Heroin is one of the most frequently seized drugs in the South-Eastern Europe. Due to the position in the Balkan route, the Republic of Serbia keeps important role in suppression of the trafficking of heroin for domestic and foreign illegal market. This research is aimed to provide a good scientific approach in the field of seized heroin analysis. Two different forms of heroin are present in the illegal market, mostly in mixtures with typical "cutting" agents: caffeine, paracetamol and sugars. It was observed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 32 publications
0
6
0
Order By: Relevance
“…2019 DART-HRMS followed by multivariate statistical analysis to infer the sources of heroin samples seized in China [ 134 ]; electrochemical strategies to detect heroin in street samples without the use of electrode modifications [ 135 ]; 2020 HPLC-MS/MS method for detection and quantification of the main alkaloids in heroin [ 136 ]; 2021 development of an HPLC-MS/MS method for the quantification of the main alkaloids in heroin [ 137 ]; ATR FT-IR method for classification and determination of the concentration range of illicit heroin in seized samples [ 138 ].…”
Section: Routine and Improved Analyses Of Abused Substancesmentioning
confidence: 99%
“…2019 DART-HRMS followed by multivariate statistical analysis to infer the sources of heroin samples seized in China [ 134 ]; electrochemical strategies to detect heroin in street samples without the use of electrode modifications [ 135 ]; 2020 HPLC-MS/MS method for detection and quantification of the main alkaloids in heroin [ 136 ]; 2021 development of an HPLC-MS/MS method for the quantification of the main alkaloids in heroin [ 137 ]; ATR FT-IR method for classification and determination of the concentration range of illicit heroin in seized samples [ 138 ].…”
Section: Routine and Improved Analyses Of Abused Substancesmentioning
confidence: 99%
“…However, heroin is rarely encountered as such and often contains many impurities and adulterants, resulting in colours ranging from white to dark brown. The wide variety in purity poses the greatest risk when using heroin, due to the difficulty in dosing and thus the risk of (lethal) overdoses [ 12 , 13 ]. For illustration, a Serbian study showed a variety in purity in their sample set from 1.7 to 58.8% w / w [ 13 ].…”
Section: Introductionmentioning
confidence: 99%
“…The wide variety in purity poses the greatest risk when using heroin, due to the difficulty in dosing and thus the risk of (lethal) overdoses [ 12 , 13 ]. For illustration, a Serbian study showed a variety in purity in their sample set from 1.7 to 58.8% w / w [ 13 ]. Diluents that are often encountered in these samples are inert powders like chalk, flour, talcum powder and glucose, but also pharmacological active compounds like acetaminophen and caffeine [ 12 , 13 ].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations